Restoration and universal operation of grid-forming inverters - Sadeque, Fahmid (Kansas State University, 2022)
This dissertation presents novel control methods for frequency and voltage restoration, and universal operation of grid-forming (GFM) inverters. The developed controllers solve the technical challenges for a microgrid with multiple GFM inverters in synchronization and power-sharing, phase-angle detection under asymmetrical conditions, capability to operate in the grid-following (GFL) mode, and frequency and voltage restoration. First, two synchronization methods for GFM inverters are presented. In the output-sync method, an incoming GFM inverter synchronizes its output voltage parameters, i.e., amplitude, phase angle, and frequency, at its point of common coupling (PCC) before closing the circuit breaker. The task is uniquely performed by introducing two proportional-integral (PI) controllers that adjust the output voltage and the angular frequency of the inverter. In the controller-sync method, two sets of controller paths are run in parallel and kept synchronized to produce the same PWM reference. But, only one set of the controller is engaged at a time. The uniqueness of this method is that it allows an inverter to stay connected to the microgrid in a standby mode without injecting any power. Then, when enabled, the inverter gradually shifts to decentralized power-sharing mode without switching the controller. Finally, the controller seamlessly switches to GFM mode, where the inverters are completely independent but synchronized. Another noteworthy fact is that, unlike the output-sync method that used two sets of voltage measurements, the controller sync method only uses one set of voltage measurements. A state-space model of the GFM inverter with the controller-sync method is derived to show the stability at every mode. The efficacy of the developed methods is experimentally validated in a microgrid with both droop and virtual inertia for power-sharing. A new phase-angle detection method, called signal reformation-based direct phase-angle detection (DPD-SR), is developed that provides an enhanced phase-angle detection capability for the GFM inverter under asymmetrical conditions of the system. The developed DPD-SR can directly estimate the phase-angle by using a mathematical function. The unique signal-reformation technique used in this method can process the asymmetrical voltage measurements into a symmetrical form and extract the phase-angle of the system without using any complicated closed-loop control. The DPD-SR method is verified through hardware experiments and compared with state-of-the-art method. Eventually, a universal controller is developed that combines the feature of the controller-sync and the DPD-SR methods. Furthermore, the developed universal controller enables an inverter to operate in GFL and GFM mode is developed. With the universal controller, the inverter can inject desired active and reactive power to the grid or microgrid in GFL mode and seamlessly transit to GFM mode if islanding is detected. The universal controller has two sets of parallel paths, where one path provide GFM control and the other path provides the GFL control and synchronization. A frequency-based islanding detection is added to the developed controller. The uniqueness of the universal controller is, the two paths are always synchronized and can provide seamless GFL to GFM transition when a fault occurs. The controller’s stability is analyzed through a state-space model, and the performance of the developed controller is verified in a microgrid for grid-connected and islanded operation in this dissertation. Finally, a frequency and voltage restoration controller is developed to overcome the frequency and voltage deviation problem with the droop controller for power-sharing. In droop-controlled power-sharing, the frequency and voltage are required to deviate from their nominal values. On the contrary, the frequency and voltage of the system are expected to be regulated by the GFM inverters. This dissertation develops a threshold-based frequency and voltage restoration method for the GFM inverters without compromising the effectiveness of the decentralized power-sharing methods. The novelty of this method is that the restoration control paths are only enabled when a load change or plug-in of an inverter is identified and disabled when the frequency and voltage parameters are restored. A state-space model is developed to perform stability analysis. The developed method is compared with a timer-based method to demonstrate its superiority. The efficacy of the restoration method is verified through experiments.
Keywords: Grid forming inverters; Universal inverter control; Frequency restoration